A Study on Students’ Attitude Towards BBA Program at Janapriya Multiple Campus - Palikhe, Amin; Adhikari, Nabin Bahadur (Janapriya Journal of Interdisciplinary Studies, 2017)
Under the study on the students’ attitude towards BBA program at JMC is to study of macro level perspective of BBA program. This research article is based on primary and secondary data including 153 sampling and purposive with descriptive research designs. This program is student centered so that students’ participation is important to achieve the objective of the program. This study shows that political situation including environmental factors is major role to play for the effectiveness of BBA program. This is competitive program, immediately applicable, not use for every social group even though it is learn for being a good businessman, entrepreneur and development, being a middle level manager in the competitive world by using creative mind of the students. Need and use of different pedagogies, language efficiency and use and problems regarding to program and campus’s perception are disclosed in here. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 21-28